Women courageous : leading through the labyrinth - Breen, Jennifer Moss; Van der Steege, Madeleine; Martin, Suzanne; Glick-Smith, Judith (Emerald Publishing Limited, 2021)
Women Courageous: Leading Through the Labyrinth is a collection of true experiences by women from different parts of the world, leading in the political, academic, non-profit public, and private sectors. The stories illustrate their courage and also include a scholarly analysis to reshape our understanding of courage - how it shows up, develops, and facilitates transformation. Through this work, the editors offer a new definition: 'Courage is pushing forward, step by step, while everything is holding you back. Often unnoticed by others, courageous acts come with great emotional challenges, and also with a sense of purpose and determination. Courage is how we transform, not only ourselves but those we support and love and the work to which we have dedicated our lives.' This international group of authors weaves insights, research, and practices gleaned from walking the leadership labyrinth in their military, aerospace, public works, university, and school education, and nonprofit careers. The book offers stories of ambition, self-actualization, co-creation, as well as conflict, loss, betrayal, and healing, that will echo your own experience. The book will surprise you with new wisdom and releases fresh courage in all of us, to rise and meet the monumental challenges of this moment.